Efektivitas Pemberian Makanan Tambahan (PMT) Lokal terhadap Balita Gizi Kurang di Kecamatan Nibong - Ema Novita Sari; Hafni Zahara; Pasyamei Rembune Kala (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Malnutrition in toddlers affects their physical growth and development, leading to long-term consequences on their welfare, education, and community income. It influences economic stability, intelligence, quality of life, and the future of children. Malnourished toddlers not only have smaller bodies but also face learning difficulties, which may eventually become a societal burden. This study applied a quantitative approach using a quasi-experimental method, with pretest and posttest measurements, conducted over two months at the Nibong Community Health Center in North Aceh Regency. The study involved 75 toddlers from 20 villages, selected using total sampling. Results revealed that 69 toddlers (92%) who consumed local supplementary food (PMT) experienced weight gain, while 6 (8%) who did not, did not show any weight improvement. A statistical analysis produced a p-value of 0.000 (p < 0.05), indicating a significant relationship between the consumption of local PMT and weight gain. The findings suggest that local supplementary food significantly improves the weight of malnourished toddlers, with 92% showing weight gain. Future studies should further analyze child characteristics and PMT menus to enhance the effectiveness of these programs.